Investigating Tactics Characteristics of Mass-Start Event of Speed Skating in Pyeongchang Winter Olympics - Wang Jin,; Su Yanhong, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2021)
The mass start event is the longest cross-country skiing event added first time in the Pyeongchang Winter Olympics held in 2018. This study aimed to highlight tactics characteristics of the event by making a statistical analysis of the points and competition results of athletes who participated in this event in the Pyeongchang Winter Olympics. For this purpose, the ranks, points, lap time, and final results of 16 male and 16 female athletes were taken as research objects in the final mass-start event of speed skating of the 2018 Pyeongchang Winter Olympics. The speed and speed coefficient of this segment were calculated by Pearson correlation analysis applying the Origin 9.4 software for nonlinear curve fitting. The results showed that athletes adopted different speed pacing strategies in each race. The analysis was based on a comparison of points and speed rhythms of different rounds. This enabled to identify and optimize tactics that might improve the probability of winning the event. This study contributes significantly with both theoretical and practical implications. The study findings specify such optimization tactics to provide a theoretical basis for sports practices as well as giving practical insights important to practitioners and sports officials. The study recommends that physical fitness should be strengthened to ensure athletes' speed endurance in speed-skating; teammates should work together tactically to get rid of the impact caused by physical exertion, and a training platform should be built to train athletes.